Using Online Learning Systems to Measure Students’ Basic Teaching Skill - Setiyawati, Enik; Wulandari, Fitria; Bahak Udin By Arifin, Moch.; Erik Rudyanto, Hendra; Santia, Ika (International Journal of Engineering and Technology, 2018)
The purpose of this article is to find out the achievement of the nine basic skills of teaching students through a scientific approach at the Department of Elementary Education Teacher Education (PGSD) of the Universitas Muhammadiyah Sidoarjo and to find out the constraints found during learning through the scientific approach in the PGSD of Universitas Muhammadiyah Sidoarjo. The purpose of this research is to improve the achievement of nine basic skills of teaching students through a scientific approach at the PGSD department of Muhammadiyah Sidoarjo University. This research was conducted using classroom action research (CAR) methods. In each PTK cycle, namely cycle 1, cycle 2, and cycle 3 there are several activities carried out, which are design, action and observation, reflection, and revision. Nine basic teaching skills for students have increased from cycle I to cycle II, and from cycle II to cycle III. This is indicated by the increasing skills of conducting variation, strengthening skills, and conducting evaluation skills. Â